Hearing and vision impairment and social isolation over 8 years in community-dwelling older adults - Alison R. Huang; Thomas K. M. Cudjoe; George W. Rebok; Bonnielin K. Swenor; Jennifer A. Deal (BMC, 2024)
Abstract Background Little is known about the long-term impact of hearing and vision impairment on social isolation. This study quantifies the association between hearing, vision, and concurrent hearing and vision impairment (dual sensory impairment) and social isolation over 8 years among older adults. Methods Data were from the National Health and Aging Trends Study (NHATS), a cohort study (2011 - 2019) of U.S. Medicare beneficiaries aged 65 years and older. Social isolation was measured by a binary indicator incorporating four domains: living arrangement, core discussion network size, religious attendance, and social participation. Hearing, vision, and dual sensory impairments were measured by self-report and modeled categorically (no impairment [ref.], hearing impairment only, vision impairment only, dual sensory impairment). Associations between sensory impairments and odds of social isolation over 8 years were assessed using multivariate generalized logistic mixed models and adjusted for demographic and health characteristics. Results Among 5,552 participants, 18.9% self-reported hearing impairment, 4.8% self-reported vision impairment, and 2.3% self-reported dual sensory impairment. Over 8 years, hearing impairment only was associated with 28% greater odds of social isolation. Participants with hearing impairment only were more likely to live alone and have limited social participation. Conclusion Greater clinical awareness of hearing impairment as a risk factor for social isolation can increase opportunities to identify and aid older adults who may benefit from resources and interventions to increase social connection and mitigate social isolation.